Shaping e-book culture: analyzing the Internet message of companies operating on the book market - Kurek-Kokocińska, Stanisława (Folia Toruniensia, 2020)
The work concerns part of the problem of digital culture. The research problem lies in the area of e-book culture (bibliology and information science). It was assumed that the semantic limits of e-book culture include both what has happened and resulted in the transformation of the book itself (relating to the book) and the presence of digital forms of books in society. The aim is to present a narrower issue - e-book culture - at the end of the second decade of the 21st century on the basis of the widely available internet content. The websites of companies and institutions dealing with the introduction of e-books as a "product form of a book" (the definition of the National Library) on the market and into circulation were used. The individual websites were tracked in terms of their content, which is dispersed, and which for the purposes of the study was called Knowledge of E-Books (hereinafter: WoE-B). The adopted method of researching the content of WoE-B allowed to evaluate this material as an important source that should be taken into account as a kind of contribution to the formation of digital book culture in society. The conducted analyzes showed that the form of the participation of the market sector in shaping the culture of e-books constituted the transfer of specific knowledge devoted to this form of the book (aspects: addressee, requirements, ownership, properties, validity / advantages). A specific reconstruction of the e-book recipient’s profile was made. Three directions of shaping e-book culture were established: 1) the use of e-book technology, 2) the use of e-book technology products, 3) the advantages of e-book technology.